2013
DOI: 10.1162/artl_a_00080
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion Without a Brain: Physical Reservoir Computing in Tensegrity Structures

Abstract: Embodiment has led to a revolution in robotics by not thinking of the robot body and its controller as two separate units, but taking into account the interaction of the body with its environment. By investigating the effect of the body on the overall control computation, it has been suggested that the body is effectively performing computations, leading to the term morphological computation. Recent work has linked this to the field of reservoir computing, allowing one to endow morphologies with a theory of un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
117
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 57 publications
0
117
0
Order By: Relevance
“…For the controller to learn to deal with its own errors, we add a second training phase, with RLS still active. In this stage, the output signals sent to the motors are mixtures of the target signals and the signals generated by the linear transformation [17]. The fraction of the target signals is reduced over time until it becomes zero.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the controller to learn to deal with its own errors, we add a second training phase, with RLS still active. In this stage, the output signals sent to the motors are mixtures of the target signals and the signals generated by the linear transformation [17]. The fraction of the target signals is reduced over time until it becomes zero.…”
Section: Methodsmentioning
confidence: 99%
“…In earlier work [9], [17], it was shown that for a tensegrity robot, a linear transformation from the sensor signals to the motor signals was enough to generate stable locomotion. The idea behind this is that the body of the robot itself has computing power, and that this power is being harvested by using it as a reservoir.…”
Section: A Embodied Computationmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical reservoirs comprise several hundred nodes, a complexity readily present in physical systems. Full analog physical implementations such as water ripples [12], mechanical oscillators [26], tensegrity structures [27,28], soft bodies [29], and the optical devices and circuits which are the subject of this review have all been implemented. RC has indeed grown to include systems which are not necessarily based on a network topology of discrete components.…”
Section: The Hardware Reservoirmentioning
confidence: 99%
“…The spirit of the morphological computation literature that follows the "offloading" or "trade-off" perspective, is that complex (highly dimensional, dynamic, nonlinear, compliant, deformable, "soft" ) bodies are advantageous for control because they can take over the "computation" that a controller would otherwise have to perform (e.g., [15,16,39] or [9] explicitly in Fig. 1).…”
Section: Simple or Complex Bodies?mentioning
confidence: 99%